2007
DOI: 10.1097/mbc.0b013e3282f1012d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiretroviral therapy on hemostasis in Brazilian pregnant women with HIV infection

Abstract: Clinical observation shows pregnant women under antiretroviral therapy present bleeding episodes at delivery, although this therapy promotes a decrease in fibrinolysis in nonpregnant patients, suggesting a prothrombotic state in the former. Since these drugs provoke hepatic disorders, they can cause bleeding disturbances. We investigated effects of antiretroviral therapy on hemostasis in pregnant women. Two groups were studied: pregnant women with HIV (n = 11), and (control) pregnant women without HIV (n = 7).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 21 publications
1
12
1
2
Order By: Relevance
“…23 A further study found that HIV patients on ART had increased levels of tissue plasminogen activator antigen and plasminogen activator inhibitor type 1, which suggests increased fibrinolysis. 9 Our study found no between-group difference in fibrinolysis as assessed by the LY-30, despite the fact that our patients were receiving ARV therapy. 12 The findings of our study, comparing the coagulation status using TEG of HIV-positive and -negative patients, suggests that in asymptomatic HIV-positive patients, routine laboratory or point of care coagulation studies are not indicated before regional anaesthesia.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…23 A further study found that HIV patients on ART had increased levels of tissue plasminogen activator antigen and plasminogen activator inhibitor type 1, which suggests increased fibrinolysis. 9 Our study found no between-group difference in fibrinolysis as assessed by the LY-30, despite the fact that our patients were receiving ARV therapy. 12 The findings of our study, comparing the coagulation status using TEG of HIV-positive and -negative patients, suggests that in asymptomatic HIV-positive patients, routine laboratory or point of care coagulation studies are not indicated before regional anaesthesia.…”
Section: Discussioncontrasting
confidence: 52%
“…13,14 Pregnancy is associated with an increase in pro-coagulant factors (II, VII, VIII, X and XI) and a decrease in anti-coagulant factors (Protein C and S, and Antithrombin III). 4,9 Fibrinogen levels rise from 28 weeks gestation, and D-dimer levels are raised throughout pregnancy. These haematological occurrences are thought to be a physiological adaptation to minimise blood loss during childbirth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAART treatment reduces the production of lupus anticoagulant, and thus HIV-infected individuals who were taking HAART have lower lupus anticoagulant than HAART-naïve subjects [43]. In this study, APTT value of HAART-naïve study subjects was higher than that of HAART groups, though the difference was not statistically significant ( P = 0.074).…”
Section: Discussionmentioning
confidence: 52%
“…Зміни гемостазу у ВІЛінфікованих вагітних на тлі АРВТ і хіміопрофілактики, згідно з літературними дани [2]. Згідно з дослідженнями de Andrade C. M. et al [3] у вагітних жінок, які отримували антиретровірусні препа рати, при пологах відзначалися епізоди кровотеч за ра хунок активації фібринолізу, що пояснюється токсичною дією препаратів на функцію печінки. Токсичне ураження печінки зазвичай розвивається протягом перших тижнів від початку хіміопрофілактики.…”
unclassified